PAX6 gene variations associated with aniridia in south India - Shashikant Shetty; Vijayalakshmi Perumalsamy; Krishnadas Subbaiah; Neethirajan Guruswamy; Sundaresan Periasamy (BMC, 2004)
Abstract Background Mutations in the transcription factor gene PAX6 have been shown to be the cause of the aniridia phenotype. The purpose of this study was to analyze patients with aniridia to uncover PAX6 gene mutations in south Indian population. Methods Total genomic DNA was isolated from peripheral blood of twenty-eight members of six clinically diagnosed aniridia families and 60 normal healthy controls. The coding exons of the human PAX6 gene were amplified by PCR and allele specific variations were detected by single strand conformation polymorphism (SSCP) followed by automated sequencing. Results The sequencing results revealed novel PAX6 mutations in three patients with sporadic aniridia: c.715ins5, [c.1201delA; c.1239A>G] and c.901delA. Two previously reported nonsense mutations were also found: c.482C>A, c.830G>A. A neutral polymorphism was detected (IVS9-12C>T) at the boundary of intron 9 and exon 10. The two nonsense mutations found in the coding region of human PAX6 gene are reported for the first time in the south Indian population. Conclusion The genetic analysis confirms that haploinsuffiency of the PAX6 gene causes the classic aniridia phenotype. Most of the point mutations detected in our study results in stop codons. Here we add three novel PAX6 gene mutations in south Indian population to the existing spectrum of mutations, which is not a well-studied ethnic group. Our study supports the hypothesis that a mutation in the PAX6 gene correlates with expression of aniridia.